Origami teaching strategy and student retention of geometry concepts - Kebin, Odesephni Bestman (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
This study investigated the effect of the origami teaching strategy on students’ retention in geometry in secondary schools in Rivers State. Three research questions and three hypotheses guided the study. The study adopted a quasi-experimental design. Simple random sampling was used to select a sample size of one hundred (100) SS2 students for this study. The population for this study was 6961 students. The instrument for data collection was the Geometry Achievement Test (GAT). Data collected were analyzed using mean and standard deviation for the research questions, while ANOVA was used to test the hypotheses. The findings revealed that the use of origami proved superior to conventional instruction in promoting students' performance and enhancing students' retention of geometry concepts. It also showed that male students performed better than female students in retaining concepts taught in geometry using the origami teaching strategy. Based on the findings, the following recommendations were made: the use of origami should be adopted in the teaching of geometry at the primary, secondary, and tertiary levels of education. Seminars, workshops, and conferences should be held on how origami can be used effectively by mathematics teachers in the teaching and learning of mathematics.